Detection of Bovine Leukaemia Virus Antibodies and Proviral DNA in Colostrum Replacers. Issue 5 (22nd November 2013) - Choudhury, B.; Finnegan, C.; Phillips, A.; Horigan, M.; Pollard, T.; Steinbach, F.
Summary Great Britain has been bovine leukaemia virus (BLV) disease free since 1999. We recently reported three separate incidents of BLV seropositivity on farms with home‐reared cattle due to the use of colostrum replacer rather than infection with BLV (Emerg. Infect. Dis., 19, 2013, 1027). These cases were all linked via the use of the same brand of colostrum replacer. Here, we investigate further by examining multiple brands of colostrum replacer for proviral DNA and BLV antibodies. BLV antibodies were detected in 7 of the colostrum replacers tested, with PCR concurring in two cases. Thus, the use of these BLV antibody‐positive colostrum replacers may also lead to false‐positive serological diagnostics.